Le fantastique clinique dans les récits de l’étrangeté psychique de Guy de Maupassant - Gadomska, Katarzyna (Studia Romanica Posnaniensia, 2001)
The present work is a study of the clinic fantastic literature in the short stories by one of the most famous 19th century authors Guy de Maupassant. In 19th century the tendency to reject the traditional fantastic literature consisting in unexpected and sudden interference of the supernatural powers into the real world.